ズワイガニ ノ キンニクシツ オヨビ カンスイゾウチュウ ノ ペプチド ニツイテ - 宮川, 正美; ミヤガワ, マサヨシ; 平林, 務; ヒラバヤシ, ツトム; 平野, 学; ヒラノ, マナブ; 村尾, 卓哉; ムラオ, タクヤ; 大塚, 譲; オオツカ, ユズル; Miyagawa, Masayashi; Hirabayashi, Tsutomu; et al. (鳥取大学教育学部, 1990)
departmental bulletin paper